Post-pandemic excess mortality of COVID-19 in Hong Kong: a retrospective studyResearch in context - Kehang Li; Yuchen Wei; Chi Tim Hung; Carlos King Ho Wong; Xi Xiong; Paul Kay Sheung Chan; Shi Zhao; Zihao Guo; Guozhang Lin; Qiaoge Chi; Carrie Ho Kwan Yam; Tsz Yu Chow; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: As the COVID-19 pandemic shifted into the post-pandemic period in early 2023, following the COVID-19 normalization with relaxation of stringent control measures and high vaccination coverage in Hong Kong, its long-term impact on mortality remains challenging with necessary needs of data-driven insights. This study examined the pattern of post-pandemic excess mortality in Hong Kong. Methods: We analyzed weekly inpatient death data from public hospitals from January 1, 2013, to June 1, 2024, using a mixed model with over-dispersed Poisson regression. Expected mortality was estimated as the difference between observed mortality and baseline derived from pre-pandemic data. Age-stratified analyses of overall and cause-specific mortality were conducted across the pre-Omicron pandemic, Omicron, and post-pandemic periods. Findings: In the post-pandemic period, the excess mortality declined but remained six-fold higher (37.66 [95% CI: 32.72–42.60] per 100,000) than pre-Omicron level, maintaining significance after adjusting for age (32.79 [95% CI: 28.13–37.46] per 100,000). The older population experienced sustained excess mortality, with crude estimates of 100.51 and 586.74 per 100,000 among those aged 65–79 years and ≥80 years, respectively, primarily due to respiratory diseases. Younger population showed near-zero overall excess mortality, whereas increased excess mortality among them occurred in heart disease, cerebrovascular disease, and injuries. Interpretation: Our findings highlight the lasting mortality impact of pandemic among vulnerable populations, specifically the older population, possibly due to the post-COVID conditions and circulating COVID-19, suggesting the need for targeted interventions for this group. Funding: Health and Medical Research Fund.